Problematyka relacji Belgradu i Prisztiny w kontekście akcesji Serbii do Unii Europejskiej .......... 139 - Krata, Cezary (Oblicza dyplomacji, 2025)
THE ISSUE OF BELGRADE AND PRISTINA’S RELATIONS REGARDING SERBIA’S EU INTEGRATIONAL PROCESSThe article presents the issue of relations between Serbia and Kosovo in the context of Serbia’s integration process into the European Union. It discusses the mutual relations between Belgrade and Pristina, the historical background which led to these relations and their impact on today’s relations between the two states, especially regardin the European Union’s efforts to make this dialogue sustainable.